Experimental caprine coccidiosis: the pattern of changes in antioxidant micronutrients and vitamins (Veterinary Science Development, 2014)
This study aimed at investigating the status of non-enzymatic antioxidant agents during experimental caprine coccidiosis. A total of 20 newborn kids were selected and allocated into 2 (diseased and healthy) groups. Ten of the kids were infected with sporulated oocysts of the most pathogenic species of Eimeria and ten served as controls. Blood samples were taken at 0 (before inoculation), 3, 7, 14, 21, 28 and 35 days post infection (dpi) and the concentrations of antioxidant trace elements, antioxidant vitamins and ceruloplasmin were measured. Our data showed remarkable reductions in serum concentrations of some antioxidant trace elements (zinc, manganese and selenium) and vitamins (vitamin C) in the diseased kids, however, significant increases were observed in the serum level of ceruloplasmin in infected animals. These alterations became more prominent at 14 to 21 dpi. These observations suggest that Eimeria parasites can significantly interfere with the levels of some antioxidant trace elements and vitamins during caprine coccidiosis. These changes indicate the overproduction of oxidative radicals during the pathogenesis of Eimeria species that may account for extensive oxidative damage in infected animals.